Experiencing cultural heritage sites using 3D modeling for the visually impaired - Themistocleous, Kyriacos; Agapiou, Athos; Hadjimitsis, Diofantos G. (My University, 2016)
There is a need to make cultural heritage sites accessible to all individuals, including those who are visually impaired. 3D printing technology provides the capability to print models of cultural heritage structure as teaching tools for the visually impaired. As well, Unmanned Aerial Vehicles (UAVs) have undergone significant advances in equipment capabilities and now have the ability to obtain high resolution images in a cost effective and efficient manner in order to create 3D models for 3D printing. This paper explores the use of UAVs to acquire high resolution images to generate 3D models that are printed using lowcost 3D printers intended to serve as a teaching aid for the visually impaired. A case study is presented for the Curium archaeological site.
Keywords: 3D images; 3D models; 3D printing; Cultural heritage; UAV